Ultrasound-Assisted Liquid-Liquid Extraction for Analyzing Methadone in Urine Samples by Gas Chromatography-Mass Spectrometry - Ahmad Shekari (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Methadone abuse and dependence are a growing concern in some countries. The present study developed and validated a rapid, simple, easy, and sensitive method for analyzing methadone in urine specimens. This approach was intended for use in clinical and forensic toxicology and drug screening laboratories. Methods: We determined methadone in urine samples by Gas Chromatography / Mass Spectrometry (GC / MS). Besides, we used Ultrasound-Assisted Liquid-Liquid Extraction (UALLE) method for the extraction and preconcentration of methadone before analysis. Results: The detection limit was 2.1 ng/mL and the limit of quantification equaled 7 ng/mL. The methadone calibration curve was linear and ranged from 7 to 10000 ng/mL, and the correlation coefficient was calculated as 0.9984. The tested method was accurate and precise. Recovery fell in the range of 81.3% to 97.4% and the enrichment factor was measured as 8.7. The method was successfully used for determining methadone in real clinical and postmortem urine samples. Conclusion: The presented method was a rapid, easy, simple, and sensitive procedure; thus, it could be applied in clinical and forensic toxicology laboratories as a routine approach for analyzing methadone.